Kolusi Pintu Awal Korupsi : Perlu Pendekatan Etika Administrasi Dan Norma Hukum - Budiman Widodo; Winarti Winarti (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2022)
Corruption prevention should be done earlier starting from its entrance, collusion. Collusion so far belongs to the classification of ethical violation but touches inadequately the violation of legal norm, because collusion practice can be done during the occupation process. It is this that gives the actor of collusion an opportunity of using the aspects that are not touched by the existing norms of law. This research used qualitative analysis method through observation, interview, and literature review. The result of research shows that corruption by means of collusion is categorized into ethical violation only. Collusion case is conducted in the process of electing the officials, before the election of legislative members or regional leaders. Intersection occurs between prospect public official and capital power.